A Rapid Method for Obtaining the Transgenic Roots of Crassulaceae Plants - Lan Zhou; Yulu Yang; Anket Sharma; Vijay Pratap Singh; Durgesh Kumar Tripathi; Wona Ding; Muhammad Junaid Rao; Bingsong Zheng; Xiaofei Wang (Plants)
Crassulaceae plants are valued for their horticultural, ecological, and economic significance, but their genetic improvement is hindered by the absence of efficient and stable genetic transformation methods. Therefore, the development of a tailored genetic transformation method is crucial for enhancing the progress of the genetic improvement of Crassulaceae plants. The results indicate that, in the transformation experiments conducted on Kalanchoe tetraphylla, the K599 strain exhibited the highest transformation efficiency (76.67%), while C58C1 was least efficient (21.43%). An acetosyringone concentration of 100 μM was optimal for the hairy root transformation, and the immersion method yielded the highest efficiency. Additionally, the Silwet L-77 concentration significantly influenced the transformation efficiency, with 0.05% leading to a decrease. Upon four Crassulaceae species, notable differences were observed, with K. tetraphylla exhibiting the highest efficiency of 100%, and Sedum alfredii displaying the lowest efficiency of 5%. The RUBY reporter gene offers a more distinct advantage over GFP in observing the transformation effects. This study developed a simple, feasible, and cost-effective method for obtaining transgenic roots from leaves of Crassulaceae. The methodology provides technical support for the genetic improvement and gene function research of Crassulaceae plants.